A model for the spatial organization and evolution of the CIA pathway in Toxoplasma gondii and related eukaryotes. - Evie R. Hodgson (21866946) (2025)
(A) Models for the spatial organization of the CIA pathway in T. gondii and related organisms. A sulfur-containing product of the mitochondrial ISC pathway (possibly a [2Fe-2S] cluster) is exported from the mitochondrion. [4Fe-4S] clusters assemble on the NBP35 scaffold (N35) at the mitochondrial outer membrane, with electrons for this process donated from NADPH via mitochondrial Tah18 (T18) and possibly Dre2 (D2). [4Fe-4S] clusters are transferred from the NBP35 scaffold to Nar1 (N1), and further to the CIA targeting complex (CTC) comprised of CIA1 (C1), CIA2 (C2) and MMS19 (M19). CIA1 contains an extended CD5 loop (green) that mediates localization of the entire CTC to the mitochondrion. The CD5 loop may bind to (i) outer mitochondrial membrane lipids or (ii) outer mitochondrial membrane accessory proteins, and place the CTC in position to receive FeS clusters from Nar1. Alternatively, (iii) the CD5 loop may mediate interactions with FeS client proteins that are anchored on the mitochondrial outer membrane, thus facilitating FeS transfer from the CTC to these proteins. Elements of the diagram were created in BioRender. Hodgson, E. (2025) https://BioRender.com/ecxz792. (B) Western blots measuring the incorporation of puromycin into proteins from rTgCIA1-mAID-HA/cTgCIA1ScCD5-Ty1 (ScCD5) or rTgCIA1-mAID-HA/cTgCIA1CD5-to-CD1-Ty1 (CD5-to-CD1) parasites cultured in the absence (−) or presence (+) of IAA for 24 h, separated by SDS-PAGE and probed with anti-puromycin and anti-TgTom40 antibodies. (C) Relative abundance of puromycin incorporation from (B) was determined as a percentage of the -IAA control for each parasite line, with abundances normalized using the TgTom40 loading control. Data points represent the mean ± SD of three independent experiments. Data were analyzed using a one-way ANOVA followed by Tukey’s multiple comparisons test, with relevant p values shown. The numerical data underlying this Figure can be found in S1 Data. (D) An illustrative phylogenetic tree adapted from currently accepted models of eukaryotic evolution [63–65]. Mitochondrial targeting domains for key components of the CIA machinery, including the extended CD5 loop of CIA1, the N-terminal (N-term) transmembrane domain (TMD) of NBP35 and the C-terminal (C-term) TMDs of the FeS proteins Elp3 and RlmN, all evolved early in myzozoan evolution, subsequent to their divergence from the ciliate lineage. The endosymbiotic acquisition of a chloroplast also occurred early in myzozoan evolution.